Stratosphere/troposphere joint variability in southern South America as estimated from a principal components analysis - Yuchechen, Adrian Enrique (2017)
To understand how the tropopause annual evolution relates to the troposphere and lower stratosphere over southern South America, the study analyzes the joint behavior of single and double thermal tropopauses with the 500 and 100 hPa levels in the region. Radiosonde data spanning the period 1973–2014 were used. Geopotential height time series that were filtered known cycles were used as input for an unrotated S-mode principal components analysis. The first three leading modes of variability were analyzed. The first one has a strong semi-annual behavior, linked to wind cycles, with maximum activity in the center of the study region on the lee of the Andes. It appears to be linked to the vertical propagation of planetary and gravity waves. Semi-annual and terannual cycles dominate the second mode, the associated spatial patterns having strong resemblance with the occurrence of cold fronts. The annual time series for the third mode are coupled to a blocking index over the South Atlantic, and the associated spatial structures are also similar to blocking patterns. Results are in good agreement with observations, showing that the use of thermal tropopauses is a valid tool for studying different phenomena taking place in the region.